SOSIALISASI PEMANFAATAN LIMBAH BATOK KELAPA MENJADI BAHAN BAKAR BRIKET DI DESA LAPA LAOK KECAMATAN DUNGKEK KABUPATEN SUMENEP - Jamilah Jamilah; Mulyadi Mulyadi; Suhartatik Suhartatik; Sabarudin Ahmad; Khoirul Hidayat; Koko Joni (Jurnal Abdimas Bina Bangsa, 2023)
In everyday life, energy is a crucial factor that supports human survival. Energy is a non-renewable resource, and energy supplies dwindle over time. Therefore, if this situation continues, humans will lose access to energy sources. Coconut shells have been chosen as an energy alternative because they have a high calorific value when compared to other biomass sources. This program involves Bumdes and PKK women in Lapa Laok village with the aim of training them in making briquettes from coconut shell waste. The results can be used as a fuel source to replace kerosene and gas, as well as creating business opportunities for unproductive residents. This training was carried out by presenting material and practice on how to process coconut shell waste into briquettes using a simple method. This activity has a double benefit, namely training people to convert coconut shell waste into briquettes which have economic value and can be used as fuel to replace kerosene and gas